Retrospective analysis of inferior vena cava collapsibility with point of care ultrasound and urine sodium and FENa in patients with early stage acute kidney injury. Issue 5 (13th October 2017) - Babar, Faizan; Singh, Gurkeerat; Noor, Mustafa; Sabath, Bruce
ABSTRACT: Early stage acute kidney injury (AKI) is an independent risk factor for an increase in mortality. Accurate assessment of volume status is a major challenge during the early stages of acute renal injury. Determining volume status based on the history and physical exam lacks accuracy. Urine sodium and free excretion of sodium (FENa) provide objective evidence of intravascular volume status when interpreted carefully and is helpful to delineate prerenal from intrinsic renal failure. In recent years point of care ultrasound has been used to assess volume status. Our team conducted a retrospective chart review to assess the association of inferior vena cava collapsibility by point of care ultrasound (POCUS) and urine electrolytes (urine sodium, fractional excretion of sodium) during early stage AKI (Stage 1–2 of KDIGO guidelines). We reviewed 150 cases based on the provisional diagnosis. 36 patients met the criteria for further review. Using bivariate analysis, we found a strong association between >50% IVC collapsibility with FENa < 0.4% with an odds ratio 5.3 (CI 1.1–24.5, p  = 0.04), and urine sodium <20 meq/dl with an odds ratio of 6.7 (Cl 1.5–30, p  = 0.02). Subsequently, multivariate analysis and Spearman correlation showed an inverse relation between IVC collapsibility and fractional excretion of sodium FENa (β = −0.4, p  = 0.001) and ( r  = −0.44, p  = 0.01). These findings suggest the role of POCUS and urinary markers in determining the intravascular volume status in AKI. POCUS is also valuable to assess volume status in cases of renal failure where urine studies are difficult to interpret.